For profit medicine: the good, the bad, and the ugly faces of offshore medical education - Ghebre, Yohannes T. (Frontiers in Education, 2025)
In recent decades, a large number of students from the United States, Canada, and, to a lesser extent, other countries have pursued medical education at offshore for-profit medical schools, primarily in the Caribbean. Although these schools offer an alternative path into the medical profession for students who may not be admitted to domestic medical schools, this pathway is confounded by risks and controversies. This article explores the good, the bad, and the ugly faces of the for-profit offshore medical school model, while drawing distinctions between regional and for-profit institutions and highlighting regulatory, legal, and socioeconomic differences across Caribbean jurisdictions.